Optimization of dairy treatment process with transglutaminase in the manufacture of fresh cheese - Pham Thi Hoan; Pham Kim Chi; Pham Thanh Tung; Trinh Khanh Son (Journal of Technical Education Science, 2020)
Microbial transglutaminase (MTGase) is an enzyme widely used in food industry. In this study, MTGases had been applied to produce fresh cheese made from whole milk powder. A set of 18 experiments was carried out to evaluate the influence of factors in reconstituted milk treatment with MTGase. A response surface methodology was applied to evaluate quality properties of fresh cheese via objective functions of hardness, yield, protein content, total solid content and sensory evaluation score. In this model, three factors were enzyme concentration (0.6 - 3.0 U/g protein), temperature (30 - 60oC), reaction time (1.5 - 6 h). The results showed that all objective functions reached the optimal values at treated enzyme concentration, temperature and reaction time of 2.59 U/g protein, 36.14oC and 4.53 h, respectively. Under enzymatic treatment, scanning electronic micrographs (SEM) also showed that the network structure of the experimental products became more uniform. The quality properties of fresh cheese (sensory evaluation score, syneresis, acidity and the total number of lactic acid bacteria) met the CODEX STAN 243-2003 revised 2010 for fresh cheese products.